Targeted ferroptosis of myofibroblasts by tubeimoside I attenuates hypertrophic scar formation - Wang, Jianzhang; Wang, Chen; Jia, Yulei; Chen, Fengchao; Wang, Youbin; Du, Juan (Frontiers in Pharmacology, 2025)
BackgroundHypertrophic scar (HS), the skin fibroproliferative disease, occurs after burn injury, traumatic injury, and surgery, resulting in high medical and economic burdens. Tubeimoside-I (TBMS1), a triterpenoid saponin monomer obtained from the Chinese medicinal herb Tubeimu, has demonstrated therapeutic potential in various diseases. In the present study, we explored the therapeutic effect of TBMS1 in the progression of HS.MethodsIn vitro studies tested the effects of TBMS1 on the biological behaviors of hypertrophic scar fibroblasts (HSFs) were investigated by cell counting kit-8, flow cytometry, wound healing, transwell, and collagen gel contraction assays. Further, the regulatory mechanism of TBMS1 in alleviating HS was elucidated. In vivo experiments were utilized to reveal the influences of TBMS1 on HS formation.ResultsIn vitro studies indicated that TBMS1 hindered HSFs proliferation, migration, and myofibroblast activation. The PI3K/AKT signaling pathway mediates TBMS1-induced ferroptosis, which was accompanied by altered expression of NRF2, SLC40A1, and GPX4, ultimately suppressing cell proliferation and collagen synthesis. In vivo experiments confirmed that local TBMS1 injection exerted potent antifibrotic effects.ConclusionThis study revealed the effect of TBMS1 in activating ferroptosis, suggesting that inducing ferroptosis is probably a novel therapeutic strategy for hypertrophic scar.